Analysing the association between perceived knowledge, and attitudes on Lassa Fever infections and mortality risk factors in lower Bambara Chiefdom - Abu-Bakarr S. Kamara; Andrew Moseray; Patrick Fatoma; Alhassan Mayei; Joseph Lamin; Osman Sankoh; Mohamed Kemoh Rogers (BMC, 2024)
Abstract Background Lassa fever (LF) presents significant public health challenges in Sierra Leone, particularly in the Lower Bambara Chiefdom. This study aims to deeply understand how knowledge and attitudes towards LF correlate with community-driven prevention and control measures. Methods A descriptive cross-sectional quantitative approach was used to conduct the research. Data from 2167 participants were collected using an Android-based survey from 1st February 2022 to 14th February 2022. Respondents' knowledge of LF causes, risk factors, transmission modes, and preventive measures were evaluated through a multiple-choice questionnaire, and attitudes toward prevention and control were measured on a 5-point Likert scale. Quantitative data were analyzed using SPSS version 26.0 and frequencies were presented in count, percentage, and table. Chi-square statistics were used to test for associations. Results Among the 2167 participants, over half were males (1184, 54.60%), farmers (1406, 64.90%), married (monogamous) (1428, 65.90%), and had never attended school (1336, 61.70%). Respondents demonstrated high knowledge levels of LF across socio-demographic groups (33% to 100%) and shared a positive attitude towards prevention and control (mean score of 26.77 on a 5-40 scale). Educational level, religious beliefs, and occupational status significantly influenced LF knowledge (p < 0.05). Specifically, illiterates had a high knowledge score of 48.24%, while those with tertiary education had the highest score at 83.33%. Additionally, a Pearson correlation analysis revealed a positive linear relationship between the degree of knowledge and positive attitude towards LF infection and mortality risk factors (r = 0.090, p = 0.02). Conclusion High LF knowledge in Lower Bambara Chiefdom positively influences prevention attitudes. Education, religion, and occupation are key factors. Tailored interventions enhance public health efforts.